2008
DOI: 10.1038/oby.2007.68
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Soy Isoflavone–Aglycone Lowers Food Intake in Female Rats With and Without Ovariectomy

Abstract: Objective: Estrogens downregulate eating behavior, and soy isoflavones are known to be estrogenic agents. We aimed to examine whether the estrogenic property of soy isoflavones can affect food intake and body weight. Methods and Procedures: Seven-week-old male, female, and ovariectomized (OVX) Sprague-Dawley rats were given free access to a diet containing 100-300 mg total isoflavone/kg diet, or to a control diet, either with or without concurrent administration of estradiol by subcutaneous implantation. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 37 publications
2
30
0
4
Order By: Relevance
“…However, we have also observed that daidzein feeding and estradiol treatment significantly decreased food intake in both female LongEvans Tokushima Otsuka and Otsuka Long-Evans Tokushima Fatty (CCK1R-deficient) rats, suggesting that CCK signaling is not essential for the anorectic effects of daidzein and estradiol. 41) In rats given food on the MF3 schedule as well as rats fed ad libitum, 11) daidzein feeding significantly decreased food intake 6 days after initiation of the experiment (Fig. 2(A)), leading us to speculate that dietary daidzein as it is not able to suppress food intake by directly inducing the expression of CCK mRNA in intestinal endocrine cells.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, we have also observed that daidzein feeding and estradiol treatment significantly decreased food intake in both female LongEvans Tokushima Otsuka and Otsuka Long-Evans Tokushima Fatty (CCK1R-deficient) rats, suggesting that CCK signaling is not essential for the anorectic effects of daidzein and estradiol. 41) In rats given food on the MF3 schedule as well as rats fed ad libitum, 11) daidzein feeding significantly decreased food intake 6 days after initiation of the experiment (Fig. 2(A)), leading us to speculate that dietary daidzein as it is not able to suppress food intake by directly inducing the expression of CCK mRNA in intestinal endocrine cells.…”
Section: Discussionmentioning
confidence: 99%
“…11) Further, estradiol treatment in OVX rats recovered uterine weight to levels similar to those seen in sham rats, but daidzein feeding did not. 11) These observations suggest that anorectic effect of daidzein might be mediated by a different mechanism than estradiol. However, daidzein appears to function as selective estrogen receptor modulators 14) which are a group of estrogen receptor agonist/antagonist with tissue selective effects.…”
mentioning
confidence: 93%
See 3 more Smart Citations